Understanding volumetric capacitance in conducting polymers - Proctor, Christopher M.; Rivnay, Jonathan; Malliaras, George G. (Journal of polymer science. Part B, Polymer physics, 2016)
ABSTRACT Recent measurements in poly(3,4‐ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) films show that capacitance scales with film volume. We discuss the ramifications of this finding and propose a simple model that describes capacitance in terms of sites in which ions injected from the electrolyte replace holes that are extracted from the film by a metal contact. We propose that volumetric capacitance is inversely proportional to the average distance between these sites. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2016, 54, 1433–1436 A simple model is presented that shows how volumetric capacitance in conducting polymer films arises through the processes of cation injection and hole extraction. It is in agreement with recent measurements of volumetric capacitance in PEDOT:PSS.